Objectivation négociée et gestion contestée de l’environnement - Thomas Debril; Gaël Plumecocq; Olivier Petit (Développement Durable et Territoires)
The papers collected for the special section entitled « Characterization and Management Modes of Natural Resources » present an overview of processes of environmental qualification and management. The use of particular concepts to understand natural resources, or particular tools to manage them relates to qualification processes, which reveals a wide range of human-nature relationships. This leads us to question the diversity of actors’ competencies as well as the heterogeneity of technical devices that are negotiated among experts and frame the ways in which the environment is managed. Symmetrically, we examine the ways various modalities of management question the processes by which particular attributes are granted to the environment.